GAYA BAHASA METAFORA DALAM PUISI BULAN LUKA PARAH KARYA HUSNI DJAMALUDDIN - NFN Musayyedah (Balai Bahasa Sulawesi Selatan, 2012)
The research intends to describe language style of metaphor used by Husni Djamaluddin in his collection poems 'Bulan Luka Parah